Interspecific introgression and natural selection in the evolution of Japanese apricot (Prunus mume). (8th November 2020) - Numaguchi, Koji; Akagi, Takashi; Kitamura, Yuto; Ishikawa, Ryo; Ishii, Takashige
Summary: Domestication and population differentiation in crops involve considerable phenotypic changes. The logs of these evolutionary paths, including natural/artificial selection, can be found in the genomes of the current populations. However, these profiles have been little studied in tree crops, which have specific characters, such as long generation time and clonal propagation, maintaining high levels of heterozygosity. We conducted exon‐targeted resequencing of 129 genomes in the genus Prunus, mainly Japanese apricot ( Prunus mume ), and apricot ( Prunus armeniaca ), plum ( Prunus salicina ), and peach ( Prunus persica ). Based on their genome‐wide single‐nucleotide polymorphisms merged with published resequencing data of 79 Chinese P. mume cultivars, we inferred complete and ongoing population differentiation in P. mume . Sliding window characterization of the indexes for genetic differentiation identified interspecific fragment introgressions between P. mume and related species (plum and apricot). These regions often exhibited strong selective sweeps formed in the paths of establishment or formation of substructures of P. mume, suggesting that P. mume has frequently imported advantageous genes from other species in the subgenus Prunus as adaptive evolution. These findings shed light on the complicated nature of adaptive evolution in a tree crop that has undergone interspecific exchange of genome fragments with natural/artificial selections. Significance Statement: The study conducted genome‐wide characterization of indices for genetic differentiation and identified fragmental interspecific introgressions in woody crops, focusing on Japanese apricot ( Prunus mume ) and related species in the subgenus Prunus (e.g., apricot [ Prunus armeniaca ] and plum [ Prunus salicina ]). Importantly, introgressed regions often underwent strong positive selection in the paths of domestication or variety differentiation, indicating that the Japanese apricot has frequently imported advantageous genes from other species.